Impact of Corporate Social Responsibility on Corporate Reputation of Public Sector Commercial Banks in Nepal - Kanauje, Sarmila; Ghimire, Tikaram (Apex Journal of Business and Management, 2024)
This study delves into the integral role of Corporate Social Responsibility (CSR) in shaping corporate reputation, focusing on public sector commercial banks (PSCBs) in Nepal. A sample of 105 banking professionals from Nepal Bank Limited (NBL), Rastriya Banijya Bank (RBB), and Agriculture Development Bank Limited (ADBL) participated, offering insights into CSR practices by employing a well-structured 5-point Likert scale questionnaire. The research elucidated that CSR activities undertaken by PSCBs were positively perceived by respondents, who concurrently acknowledged the commendable corporate reputations of their organizations. Notably, community responsibilities (β = 0.492, p-value < 0.001, 95% CI: 0.278 - 0.707) and investor responsibilities (β = 0.221, p-value = 0.01, 95% CI: 0.054 - 0.388) emerged as significant contributors to enhancing corporate reputation among the six CSR practices examined. To measure the impact, simple and multiple regression analyses were employed, affirming the positive association between CSR initiatives and corporate reputation. This research underscores the pivotal role of CSR, particularly in community and investor engagements, as a catalyst for bolstering the corporate reputation of PSCBs in Nepal. These findings offer valuable insights for organizational strategy and underscore the reciprocal benefits of responsible business practices.